Tuberculosis presenting as a 'swollen calf'. (23rd November 2016) - Kotecha, Deevia; Sardar, Mini; Latimer, Mark David
Abstract : We report the case of an 83-year-old man who presented with swelling of his left lower leg. Subsequent investigations revealed that the swelling was due to a Mycobacterium tuberculosis abscess in the tibialis anterior muscle.